LL-VNS attenuates SK2 expression and incidence of arrhythmias following acute myocardial infarction in rats - Chen, Mingxian; Zhu, Tongjian; Wu, Zhihong; Hu, Lin; Wu, Zhijian; Liu, Qiming; Zhou, Shenghua (Frontiers in Cardiovascular Medicine, 2023)
Objectives Our previous study has demonstrated that low-level vagus nerve stimulation (LL-VNS) protects the heart against ventricular arrhythmias (VAs) induced by acute myocardial infarction (AMI). However, the potential mechanisms by which it influences ventricular electrophysiology remain unknown. Materials and methods Forty-five rats were divided into three groups: a Control group (sham AMI followed by sham LL-VNS, n = 15), an AMI group (AMI followed by sham LL-VSN for 60 mins, n = 15), and an AMI + LL-VNS group (AMI followed by LL-VSN for 60 mins, n = 15). Heart rate variability (HRV), ventricular effective refractory period (ERP), ventricular fibrillation threshold (VFT), and left stellate ganglion (LSG) activity were measured at baseline and during AMI. Finally, myocardial tissues were collected for tissue analysis. Results AMI directly induced hyperactivity in the LSG and reduced vagal tone as indexed by HRV. AMI also decreased VFT, and shortened ERP but increased ERP dispersion. AMI resulted in an increase in expression of ventricular small-conductance Ca2+-activated K+ (SK2). However, LL-VNS significantly mitigated or eliminated the effects of AMI. Conclusion LL-VNS altered the electrophysiological properties of the ventricles through inhibition of cardiac sympathetic nervous activity and reduction in SK2 expression.